Description of Children's Anxiety with Post Traumatic Stress Disorder as the Impact of Natural Disasters Tornado - Ulfah Nur Hanifah; Arum Pratiwi (Jurnal Ilmu Keperawatan Jiwa, 2020)
Puron Village children who experience traumatic event of a tornado manifest variety of psychological and behavioral symptoms. The phenomenon that occurs in Puron Village children after whirlwind event children experience anxiety disorders, panic and fear of cloudy clouds and rainwater when it rains. This condition will get worse if not handled properly, therefore an early detection of anxiety with PTSD is needed as a result of tornado disaster. The aim is to identify post traumatic stress disorder incidents in children affected by a whirlwind in Puron Village, Sukoharjo Regency. The method used in this research is quantitative descriptive with a survey approach. Respondents numbered 30 children using the CPSS questionnaire in which the results of the CPSS questionnaire validity test were r count 0.949 and the realiability of r count >0.648 This study used Nonprobability sampling, namely quota sampling technique. The results of this study show a picture anxiety of children with PTSD as a result whirlwind disaster of at most 7 children (23.3%) experiencing severe PTSD, and 5 girls experiencing severe PTSD. The level anxiety of PTSD children victims whirlwind disaster suffered the most severe category PTSD by 23.3% with symptoms that arise namely symptoms of Re-Experiencing symptoms, avoidance and hyperarousal.